European public leadership in crisis? - Liddle, Joyce, 1952-; Diamond, John, 1954- (Critical perspectives on international public sector management ;, 2014)
Despite different legal and constitutional arrangements, in many states across Europe, public leaders are forging new collaborative relationships with non-state and civic actors to seek innovative ways of providing public services. Leadership varies between situations and contexts, but is still seen as central to good governance and includes individuals who will promote institutional adaptations in the public interest. There are almost as many definitions of leadership as there are writers on the subject, as it is a complex social phenomenon, lacking clear boundaries. This volume questions "what are the changing dynamics of public leadership across different European settings?" Anglo-American models of leadership have dominated and influenced current thinking. Chapters in this volume highlight emergent thinking and discussions on the strengths and weaknesses of current understandings and knowledge. Authors investigate the tensions between Anglo-American and economic focused models of leadership and emergent policy and management paradigms that may challenge received wisdom.